Taste of Home What can I bring? : 360+ dishes for parties, picnics & potlucks. (RDA Enthusiast Brands, LLC, 2023)
Need the perfect dish to pass? Rest assured, it will be a hit when it comes from What Can I Bring Cookbook! Regardless of the reason...and regardless of the season...all great parties, holidays and gatherings feature tasty foods, munchable snacks and impressive desserts. Let this all-new cookbook help you find the perfect contribution to cocktail parties, tailgates, backyard barbecues, bridal and baby showers, Christmas buffets and other events. Each recipe serves a crowd, travels well and offers the no-fuss ease today's home cooks need most. In addition to more than 360+ make-and-take dishes, you'll find packing and traveling tips, suggestions for the ideal foods to bring to specific get-togethers and other tricks for answering the popular question, "What can I bring?"